2004
DOI: 10.3168/jds.s0022-0302(04)73428-1
|View full text |Cite
|
Sign up to set email alerts
|

Production and Health of Pasture-Fed Dairy Cattle Following Oral Treatment with the Ionophore Lasalocid

Abstract: The aim of the study was to evaluate the effect of feeding the ionophore lasalocid on the productivity and health of seasonally calving, pasture-fed dairy cows. Dairy cows (n = 1020) from 4 herds were enrolled in a split-herd, prospective intervention study. Cows were blocked by breed and age, ranked on previous production, and then assigned to 2 treatment groups. Treatment cows were each exposed to 300 to 350 mg of lasalocid/d commencing 3 wk before and ending 18 wk after the start of the seasonal calving per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 37 publications
0
11
0
1
Order By: Relevance
“…The impact of monensin on reducing mastitis by 9% is a small effect but an interesting finding. Reductions in mastitis incidence with monensin treatment (Heuer et al, 2001) and for lasalocid treatment (McDougall et al, 2004) have been previously reported. The mechanism for this is most likely to be an improvement in energy metabolism, improving immune function and allowing the cow to better mount a strong defense against infection challenge.…”
Section: Discussionmentioning
confidence: 79%
“…The impact of monensin on reducing mastitis by 9% is a small effect but an interesting finding. Reductions in mastitis incidence with monensin treatment (Heuer et al, 2001) and for lasalocid treatment (McDougall et al, 2004) have been previously reported. The mechanism for this is most likely to be an improvement in energy metabolism, improving immune function and allowing the cow to better mount a strong defense against infection challenge.…”
Section: Discussionmentioning
confidence: 79%
“…It covers all classes of antibiotics, including ionophores, a group of substances extensively used as coccidiostats in poultry production and as growth promoters or production enhancers in ruminants. Ionophores improve animal performance in both dairy and beef cattle (McDougall et al, 2004;Gallardo et al, 2005;Melendez et al, 2006). In feedlot cattle in particular, their effects are well documented, with treated animals showing an increase in daily gain and feed efficiency averaging 1.6% and 7.5%, respectively (Goodrich et al, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Use of antibiotic growth promoters (ionophores) has proven to be a useful means to improve feed effi ciency and prevent rumen acidosis when ruminants are fed diets containing starch (McDougall et al, 2004;Melendez et al, 2006). Subtherapeutic use of antibi-otics is controversial and legislators in Europe have moved to prohibit their use in animal feeds (Wallace, 2004).…”
Section: Introductionmentioning
confidence: 99%